PENGEMBANGAN MEDIA EDUGAME GETAR SIDAQU BERBASIS REMO GAGRAK ANYAR PADA MATA PELAJARAN SENI BUDAYA KELAS V SDN PENJARINGANSARI 2 - Agita, Silvina Cahya Agita; Azka Arifin, She Fira (Jurnal Pendidikan Dasar, 2023)
The condition of children's interests tends to have an impact on current traditions which can eliminate cultural sustainability. So that culture is no longer left behind and teaching and learning activities are not monotonous, one way is to introduce local wisdom by using edugame learning media in the form of CAI-based quizzes. This research and development aims to determine the validity, practicality and effectiveness of the remo gagrak anyar based vibrating sidaqu edugame to improve student learning outcomes in class V arts and culture subjects at SDN Penjaringansari 2. This research is a type of R & D with the ADDIE research model. Data collection techniques use validation sheets, observations, questionnaires, tests. The research results showed that the validity of the material was 90% and the media graphics were 86% in the very valid category. The practicality of Edugame Getar Sidaqu media is based on the implementation of the teaching process at 97% in the very good or practical category. Effectiveness based on the results of the student response questionnaire reached 89% in the very good category. Keyword : Learning Media, Edugame, Learning Results